CITREX 2024 - Congratulations to all winners from PSM UMPSA - Muhammad Azrin, Ahmad (Pusat Sains Matematik (PSM), 2024)
Centre for Mathematical Sciences would like to congratulate the winners of the 14th Creation, Innovation, Technology & Research Exposition (CITREX 2024) which has been held on 8 – 9 May 2024 at Sport Complex, UMP Gambang Campus. In this exhibition, researchers submit their very best outcome of research projects, and at the same time to identify the potential projects to be participated in local and oversea exhibition.